A critical review on prospects and challenges of metal-oxide embedded g-C3N4-based direct Z-scheme photocatalysts for water splitting and environmental remediation - Suma Das; Trinayana Deka; Pujita Ningthoukhangjam; Avijit Chowdhury; Ranjith G Nair (Applied Surface Science Advances, 2022)
Solar photocatalysis is one of the most emerging feasible solutions for the prevailing energy and environmental issues in a sustainable manner. In this context, graphitic carbon nitride (g-C3N4) is evolving as a highly appropriate and intriguing material due to its fascinating physicochemical features. Low absorption range, low specific surface area (SSA), fewer active sites, high electron-hole recombination rate, and insufficient redox potentials limits its photocatalytic performance. The widely reported strategies to address the above limitations include doping, morphological tuning, type II heterojunction, Z-scheme heterojunctions etc. Among these, in recent years, Direct Z-scheme based photocatalysts has emerged as the most promising one as it maximizes the redox potential and enables effective spatial charge separation. The widely reported g-C3N4-based direct Z-scheme systems includes g-C3N4-wide band gap SCs, g-C3N4-narrow band gap SCs and g-C3N4-based ternary composite. Keeping this in mind, the current review tries to identify the challenges and future prospects of g-C3N4-based direct Z-scheme systems for energy and environmental applications. This review reveals that the g-C3N4-narrow band gap SC system is advantages over the g-C3N4-wide band gap SC system for solar photocatalytic applications as it produces larger amount of photo-generated effective charge carriers. The review found that, ternary Z-scheme system can perform better, however minute optimization at molecular level is still required. Additionally, in depth studies on the Fermi level and associated Fermi level alignment are needed for better understanding of Z-scheme systems and for its commercialization.